Bacopa monnieri: A Comprehensive Analysis of Quality Standards, Safety, and Regulatory Compliance (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
India's diverse topography and climate foster a rich repository of medicinal herbs, which includes Bacopa monnieri, whose therapeutic potential is outstanding. Traditionally rooted in Ayurvedic medicine, Bacopa monnieri is today gaining global popularity for its reputed neuroprotective, cognitive-enhancing, anti-cancer, and stress-relieving properties. Despite its increasing demands, many challenges are there to maintain quality, safety, and consistency against the backdrop of natural variability, contamination risk, and regulatory issues, even as the pressure is mounting from the global marketplace. Present research included study highlights organoleptic, microscopic, physicochemical, chromatographic, and toxicological parameters of Bacopa monnieri from standard literature and regulatory frameworks such as the Ayurvedic Pharmacopoeia of India, Indian Pharmacopoeia and the Indian Standards of Medicinal Plants. This study highlights quality challenges such as contamination with heavy metals, pesticide residues that can affect efficacy and safety of final herbal product formulation. Bioactive compounds like bacoside and bacopaside are present in Bacopa monnieri as confirmed by chromatographic profiling. This study strongly emphasizes integrated quality assessment to satisfy both Good Agricultural and Collection Practices and international safety standards. Once these challenges are met positively in their dedication, the marketability and therapeutic reliability will improve. Therefore, promote B. monnieri, further strengthening India's stature as a global leader in herbal medicine.